Synergizing Transformational Leadership and Learning Communities: A Quantitative Path to Enhancing Elementary Teacher Professionalism - Rifatun, Ana; Supandi, Supandi; Nurkolis, Nurkolis (JURNAL AL-TANZIM, 2026)
This study aims to analyze the influence of school principals’ transformational leadership and the effectiveness of learning communities on elementary school teachers’ professional competence. The background is that teachers’ professional competence is not yet optimal; it is still at a basic level. The role of the principal learning leader and the effectiveness of learning community activities are not yet evident. The research used a quantitative, correlational design. The population consisted of all elementary school teachers in Tanggungharjo District, and a sample of 137 respondents was selected using proportional random sampling. Data were collected through questionnaires that had been tested for validity and reliability, and analyzed using simple and multiple linear regression. The results of the study show that the principal’s transformational leadership has a positive and significant effect on teachers’ professional competence, with a regression coefficient of 0.710. The effectiveness of the learning community has a positive and significant effect on teachers’ professional competence, with a regression coefficient of 0.435. Transformational leadership and learning community effectiveness had a significant effect on teachers’ professional competence, with a contribution (R Square) 60.2%. An inspiring leadership style and the optimization of the learning community are key factors in improving teacher professionalism.